Microparticles and their role in coronary artery disease. (1st March 2017) - Koganti, Sudheer; Eleftheriou, Despina; Brogan, Paul A.; Kotecha, Tushar; Hong, Ying; Rakhit, Roby D.
Abstract: Despite significant advances in prevention, medical and interventional management, coronary artery disease (CAD) remains the leading cause of death worldwide. Although the number of people being diagnosed with CAD has plateaued in the western world, it is projected to increase significantly in the developing world reaching epidemic proportions, particularly in South Asia. To better stratify the risk of developing and suffering a cardiovascular event due to CAD, not only plasma biomarkers relating to disease burden but also disease activity in CAD are needed; this will allow targeting of appropriate management to high-risk patients for acute events. Over the last twenty years, data have emerged showing the role of sub-micron vesicles called microparticles (MPs) in the pathogenesis of formation and evolution of atherosclerotic plaques causing either stable angina (SA) or acute coronary syndromes (ACS). Herein we provide an overview of our current knowledge of MP formation, composition and possible mechanisms through which they could be contributing to CAD. We also reviewed currently available methods and their limitations in quantifying MPs and in determining their functional aspects. Role of various treatments ranging from dietary substitutes to oral medicines and intravenous medications to mechanistic procedures such as hemofiltration are elaborated. Although evidence implicating the role of MPs in CAD are mounting large scale prospective studies are still lacking and are the need of the hour prior to establishing the use of MPs as biomarkers for the early detection of CAD and its progression. Highlights: Coronary artery disease remains the leading cause of death across the world. Microparticles play a role in the pathogenesis of atherosclerosis. Microparticles may have a role as a biomarker in early detection of coronary artery disease.